The effect of 3D printing parameters on the tensile strength of acrylonitrile butadiene styrene filament for designing CNC router machine gears - Lazuardi, Lazuardi; Rizza, Muhammad Akhlis (Jurnal Polimesin, 2023)
Print parameters are factors that influence the mechanical strength of 3D printed objects. Based on a literature review, the parameters of layer thickness, printing speed, and fill geometry percentage value influence the mechanical strength of 3D printed objects. This study focuses on a combination of robust 3D printing parameters for designing CNC router machine gears. The purpose of this research was to determine the effect of printing parameters on the mechanical strength of tensile loads on 3D printed objects. From the experimental results, it was found that by providing a combination of layer thickness parameters, printing speed parameters, and fill percentage parameters, it has an effect on the mechanical strength resistance of 3D printed objects to accept tensile loads. From the research it was found that the ideal layer thickness parameter of 0.1 to 0.2 mm does not exceed half the size of the nozzle diameter of 0.4 mm to produce fine raster fibers. From the research it was found that the ideal speed parameter for printing gears with ABS filament material is at speed 30 mm/s to 50 mm/s to produce a stable raster fiber size and the percentage parameter of a good fill for printing gears is at a value of 20% to 40%. The results of the research found the best printing parameters for printing gears with a print parameter formula with a 3D print parameter formula layer height 0.15mm, gyroid infill 20%, with a speed of 30mm/s maximum tensile strength reaching 30.7 MPa with the results of wheel loading simulation analysis gear is able to withstand a maximum workload of 85 Kg